Pasung Behaviour for Client with Mental - Dyah Wahyuningsih; Mukhadiono Mukhadiono; Widyo Subagyo (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
This study aims to describe the behavior of people with mental disorders who are shackled in the district of Puskesmas Sokaraja II. We use qualitative fenomenology research design. The data collecting use indepth interview to 13 participants , they are families, community and health care workers. According to the research result, care service for the shackled patients including food and bath service. The reason of the family for shackling are self and environment harm, risk of killing someone, wandering around and disturbing the environment. Factors that influence shackling is that mental disorder is untreatable, dangerous, stigma that hospital care does not solve the problem, fund and health insurance factor that make them think that mental disorder is the family’s responsibility.